Higher intake of fruits, vegetables or their fiber reduces the risk of type 2 diabetes: A meta‐analysis - Wang, Ping‐Yu; Fang, Jun‐Chao; Gao, Zong‐Hua; Zhang, Can; Xie, Shu‐Yang (Journal of diabetes investigation, 2016)
Aims/Introduction Some previous studies reported no significant association of consuming fruit or vegetables, or fruit and vegetables combined, with type 2 diabetes. Others reported that only a greater intake of green leafy vegetables reduced the risk of type 2 diabetes. To further investigate the relationship between them, we carried out a meta‐analysis to estimate the independent effects of the intake of fruit, vegetables and fiber on the risk of type 2 diabetes. Materials and Methods Searches of MEDLINE and EMBASE for reports of prospective cohort studies published from 1 January 1966 to 21 July 2014 were carried out, checking reference lists, hand‐searching journals and contacting experts. Results The primary analysis included a total of 23 (11 + 12) articles. The pooled maximum‐adjusted relative risk of type 2 diabetes for the highest intake vs the lowest intake were 0.91 (95% confidence interval [CI] 0.87–0.96) for total fruits, 0.75 (95% CI 0.66–0.84) for blueberries, 0.87 (95% CI 0.81–0.93) for green leafy vegetables, 0.72 (95% CI 0.57–0.90) for yellow vegetables, 0.82 (95% CI 0.67–0.99) for cruciferous vegetables and 0.93 (95% CI 0.88–0.99) for fruit fiber in these high‐quality studies in which scores were seven or greater, and 0.87 (95% CI 0.80–0.94) for vegetable fiber in studies with a follow‐up period of 10 years or more. Conclusions A higher intake of fruit, especially berries, and green leafy vegetables, yellow vegetables, cruciferous vegetables or their fiber is associated with a lower risk of type 2 diabetes. Our results showed that a higher intake of fruit especially berries and green leafy vegetables, or yellow vegetables, or cruciferous vegetables, or their fiber, is associated with a lower risk of type 2 diabetes.